Enhancements of soil priming effect and carbon sequestration in degraded alpine meadows via supplementation: a comparative study of Tibetan sheep (Ovis aries) and plateau pika (Ochotona curzoniae) excrements - Qinyao Li; Wenquan Yang; Yanru Wu; Xilai Li; Jiancun Kou; Yanghua Yu; Yangcan Zhang; Xinting He; Yunlong Zhao (Ecological Processes)
Abstract Background Grassland degradation decreases the capacity of soil carbon sequestration, while the supplementation of exogenous organic matter enhances the soil priming effect (PE) and affects the carbon cycle in the soil. The excrements of Tibetan sheep (Ovis aries) and plateau pika (Ochotona curzoniae) play an important role in soil carbon cycling. Therefore, they were used to enrich alpine meadow soils degraded to different levels after incubation at 20 °C for up to 45 days. The PE was analyzed using the natural 13C isotope tracer method in relation to the alpine meadow soil properties. Results The supplementation of the two kinds of excrement significantly increased soil PE accumulation and soil carbon sequestration. Of the two, Tibetan sheep excrement achieved a better effect. Compared with non-degraded alpine meadow soil, severely degraded alpine meadow soil had significantly different PE, but the PE of lightly and moderately degraded meadow soil was not significantly different from each other. Structural equation modelling shows that total nitrogen (TN), soil organic carbon (SOC), β-1,4-N-acetylaminoglucosidase (NAG), β-1,4-glucosidase (βG), pH, and microbial biomass carbon (MBC) are the main factors affecting PE. In particular, TN directly negatively affected PE, SOC and the NO3 −-N:NH4 +-N ratio indirectly affected PE by affecting soil enzyme activity and MBC. Conclusions This study demonstrates that the supplement of animal excrements can improve the extracellular enzyme activity and nitrogen content in soils, which is conducive to PE and net carbon balance. Supplementation of both Tibetan sheep and plateau pika excrements can effectively enhance soil pH, further increase microbial biomass and extracellular enzyme activity, and improve soil fertility and carbon sequestration ability of seriously degraded alpine meadow soil. The NO3 −-N:NH4 +-N ratio and enzyme activity in plateau pika excrement were higher than those in Tibetan sheep excrement, which promote the soil PE in alpine meadows. The findings of this study provide theoretical evidence for the rational utilization of the excrements in the alpine meadow with different levels of degradation.